INTEGRASI KETERAMPILAN ABAD 21 DALAM MODUL SOCIOLINGUISTICS: KETERAMPILAN 4C (COLLABORATION, COMMUNICATION, CRITICAL THINKING, DAN CREATIVITY) - Winda Winda Trisnawati; Arini Kumala Sari (Jurnal Muara Pendidikan, 2019)
Preparing 21st century students to be able to compete in the future, teachers around the world promote several skills to face the challenges of 21st century development. Students need 21st century skills which are known as 4C skills (critical thinking, collaboration, communication, and creativity). Integrating 21st century skills in the learning process effectively becomes very important. Teaching material as a source of learning is needed in this regard. One of the teaching materials is a module. The aim of this research is to develop an integrated Sociolinguistics module on 21st century skills that focus on 4C skills. It aims to find out the suitable of this module as teaching material for students in the English Education Department of STKIP Muhammadiyah Muara Bungo. This research method used research and development (R&D). The research procedure was divided into two, namely preparation and implementation. This research was conducted to students in the fifth semester of the academic year 2019/2020 English Education Department of STKIP Muhammadiyah Muara Bungo. Data collection techniques used questionnaire and observation sheets as instrument. This research data analysis technique used quantitative data analysis techniques and qualitative data analysis techniques. The results showed the recapitulation of assessment aspects from various experts, sociolinguistics lecturer, student questionnaire sheets, and observations sheet. The following are the percentages of the result module eligibility which includes: the results of the material expert validation was 61.3% (good category); the results of the validation of media experts was 75.8% (excellent category); module self-evaluation results by lecturers was 90% (excellent category); field trial observation sheet results was 78.9% (excellent category); and the results of the student questionnaire sheet was 76.3% (excellent category). So the sociolinguistics module which is integrated with 4C skills is appropriate to be used in the learning process.